Biocompatibility of functionalized designer self‐assembling nanofiber scaffolds containing FRM motif for neural stem cells. Issue 5 (4th June 2013) - Zou, Zhenwei; Liu, Ting; Li, JingFeng; Li, Pindong; Ding, Qian; Peng, Gang; Zheng, Qixin; Zeng, Xianlin; Wu, Yongchao; Guo, Xiaodong
Abstract Peptide self‐assembling scaffolds have been widely used in tissue engineering. Much work has been focused on modifying the self‐assembling scaffolds with functional motifs for desired biological activities. We report here the development of a biological material designed specifically for neural tissue engineering (NTE). Using RADA‐16 (AcN–RADARADARADARADA–CONH2) as a base scaffold, we synthesized a 31 amino acid peptide RADA‐FRM (AcN–RADARADARADARADAGGSIDRVEPYSSTAQ–CONH2) containing the neural cell adhesion molecule (NCAM)‐derived mimetic peptide FRM (SIDRVEPYSSTAQ), which could undergo self‐assembly into a nanofiber scaffold. We tested the characterization of the nanofiber scaffold using atomic force microscopy (AFM) and accessed the rheological properties of FRM‐containing nanofiber scaffold (FRM‐NS). Then we examined its biocompatibility on neural stem cells (NSCs) from neonatal rats. Regrettably, we found that FRM‐NS had no effect on differentiation of NSCs. However, we tested that FRM‐NS was noncytotoxic. Furthermore, compared to pure RADA‐16 scaffold, we found that the designer self‐assembling peptide scaffold containing FRM motif could significantly promote NSCs proliferation and stimulate NSCs migration into the three‐dimensional scaffold. Our results indicate that the novel designer peptide scaffold containing FRM had excellent biocompatibility with NSCs and may be useful for central nervous tissue repair. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 1286–1293, 2014.